2017
DOI: 10.1007/s00249-016-1196-0
|View full text |Cite
|
Sign up to set email alerts
|

The small neurotoxin apamin blocks not only small conductance Ca2+ activated K+ channels (SK type) but also the voltage dependent Kv1.3 channel

Abstract: Apamin is frequently used as a specific blocker of small-conductance Ca-activated (SK type) K channels. Here we show that the small neurotoxin is not as specific as anticipated. It is also a high-affinity inhibitor with an IC of 13 nM of the Kv1.3 channel; it blocks the latter with potency similar to the Kv1.3 blocker PAP-1. Since SK type channels and Kv1.3 channels are frequently coexpressed in different tissues such as cells of the immune system, apamin must be used with caution as a pharmacological tool.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 24 publications
1
12
0
Order By: Relevance
“…Although apamin has long been used to study K Ca 2 channels, a recent study has demonstrated that it also blocksK v 1.3 channels (22). As K v 1 channels are present on the AIS, we wanted to ensure that the unbinding forces that we detected were indeed between apamin and K Ca 2 channels.…”
Section: Resultsmentioning
confidence: 99%
“…Although apamin has long been used to study K Ca 2 channels, a recent study has demonstrated that it also blocksK v 1.3 channels (22). As K v 1 channels are present on the AIS, we wanted to ensure that the unbinding forces that we detected were indeed between apamin and K Ca 2 channels.…”
Section: Resultsmentioning
confidence: 99%
“…Apamin, a highly selective SK channel blocker, does not affect human cardiac Na + , l -type Ca 2+ , or major K + currents 20 . The family of SK channels consists of three members that exhibit differential sensitivity to apamin: SK1 (also known as K Ca 2.1, encoded by the KCNN1 gene), which has the least sensitivity (EC 50 for hSK 1–10 nM), SK2 (also known as K Ca 2.2, encoded by the KCNN2 gene), which has the highest sensitivity (EC 50 ~40 pM), and SK3 (also known as K Ca 2.3, encoded by the KCNN3 gene), which has intermediate sensitivity (EC 50 ~1 nM) (Table 1 ).…”
Section: Structure and Function Of Sk Channels In The Heartmentioning
confidence: 97%
“…This peptide is a specific inhibitor of small-conductance Ca 2+ -activated K + (SK) channels in the central nervous system ( 13 , 15 ) and activates the M 2 inhibitory muscarinic receptors of the peripheral nervous system ( 10 , 14 , 15 ). Another activity is blockage of the Kv1.3 channel, a potassium channel type found in immune cells ( 24 ). Pharmacologically, apamin has antibacterial, antifungal, anti-inflammatory, anti-atherosclerotic, and antitumoral effects ( 13 ) and has been tested for treating neurological disturbances, including Parkinson's disease and learning deficit disorder ( 15 ).…”
Section: The Honeybee Venommentioning
confidence: 99%